2009
DOI: 10.1007/s12020-009-9283-y
|View full text |Cite
|
Sign up to set email alerts
|

Overactivation of NF-κB impairs insulin sensitivity and mediates palmitate-induced insulin resistance in C2C12 skeletal muscle cells

Abstract: Lipid-induced insulin resistance is associated with inflammatory state in epidemiological studies. However, it is still unclear whether the activation of NF-κB, a pivotal transcription factor of inflammation, plays a crucial role in mediating skeletal muscle insulin resistance. This study addressed what was the role of NF-κB in lipid-induced insulin resistance and whether NF-κB activation was sufficient to cause insulin resistance in C2C12 myotubes. A 16 h exposure of myotubes to palmitate reduced net insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
(40 reference statements)
4
30
0
1
Order By: Relevance
“…Pre-treatment with palmitate, a saturated fatty acid, was used to induce a state of relative insulin resistance in C 2 C 12 myotubes as previously described (Rodriguez et al, 2010;Zhang et al, 2010). Consistent with reports of others (Rodriguez et al, 2010) we show that exposure to a high fat environment lead to aberrant expression of genes that regulate skeletal muscle oxidative capacity in this cell line.…”
Section: Discussionsupporting
confidence: 88%
“…Pre-treatment with palmitate, a saturated fatty acid, was used to induce a state of relative insulin resistance in C 2 C 12 myotubes as previously described (Rodriguez et al, 2010;Zhang et al, 2010). Consistent with reports of others (Rodriguez et al, 2010) we show that exposure to a high fat environment lead to aberrant expression of genes that regulate skeletal muscle oxidative capacity in this cell line.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, several disturbances in hormone signaling, i.e. enhanced phosphorylation of protein kinase C-theta (Wang et al, 2010), increased protein tyrosine phosphatase-1B (Bakhtiyari et al, 2010), decreased phosphorylation of Akt (Feng et al, 2012) or activation of NF-kB (Barma et al, 2009;Zhang et al, 2010;Salvad o et al, 2013), usually attributed to palmitate-induced insulin resistance, could also affect myoblast differentiation. Clarification of this issue requires further investigation, involving transcriptional profiling or proteomic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid overload, especially with PA, activates NF-κB transcriptional activity, which results in subclinical inflammation and has been linked to the pathogenesis of IR in skeletal muscle [4,5]. Inhibition of NF-κB activity by pharmacological means or by use of small interfering RNA technology can ameliorate PA-induced proinflammatory cytokine expression and IR [4,5,8]. Previous data showed that oleic acid can prevent PA-induced IL-6 expression and NF-κB activation and can ameliorate PA-induced inhibition of AKT phosphorylation and glucose uptake by insulin stimulation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, activation of upstream stress kinases such as the mitogenactivated protein kinases (MAPKs) and protein kinase C-θ (PKC-θ) is involved in PA-induced NF-κB activation and proinflammatory cytokine expression in myotubes [4,5]. Moreover, inhibitors of MAPK, PKC-θ, and NF-κB can reverse PA-induced IR in skeletal myotubes [4,8].…”
Section: Introductionmentioning
confidence: 99%